2010
DOI: 10.1021/jp1030448
|View full text |Cite
|
Sign up to set email alerts
|

Potential-Induced Ordering Transition of the Adsorbed Layer at the Ionic Liquid/Electrified Metal Interface

Abstract: The potential-driven ordering transition of a LiCl layer adsorbed on the (100) surface of a metallic aluminum electrode is studied by molecular dynamics simulations. The transition causes a sharp peak in the potential dependence of the differential capacitance of the interface. This result is in qualitative agreement with recently reported experimental work on the interface between a room temperature ionic liquid and a well-defined Au(100) surface. In the LiCl/Al simulations, the transition occurs when the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
113
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 49 publications
8
113
0
Order By: Relevance
“…29 Appling a surface potential induces a re-ordering of the normal Stern layer structure to compensate the interfacial charge; the surface is enriched in anions at positive potentials and vice-versa. [29][30][31][32][33][34] This behaviour has been theoretically validated with several important computational studies modelling the ILelectrode interface. [30][31][32][33][34][35][36][37] In a landmark 2011 paper Bazant et al 38 predicted the potential dependant normal distribution of ions with focus on overscreening and crowding of ions at electrode interfaces.…”
mentioning
confidence: 54%
“…29 Appling a surface potential induces a re-ordering of the normal Stern layer structure to compensate the interfacial charge; the surface is enriched in anions at positive potentials and vice-versa. [29][30][31][32][33][34] This behaviour has been theoretically validated with several important computational studies modelling the ILelectrode interface. [30][31][32][33][34][35][36][37] In a landmark 2011 paper Bazant et al 38 predicted the potential dependant normal distribution of ions with focus on overscreening and crowding of ions at electrode interfaces.…”
mentioning
confidence: 54%
“…Charge/voltage driven structural transitions in the electrical double layer (EDL) in ionic liquids (ILs) have recently attracted large interest in experimental [1,2,3,4,5,6], theoretical [7] and computational [8,9,10,11,12,13,14] communities due to the importance of this subject for a variety of IL applications [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…60 As a common trend, the atomistic MD simulations on atomically flat, metallic electrode surfaces showed only a weak dependence of DC versus the applied potential (∆U) in the range of potentials where the electrode surface is not saturated with ions (i.e., within ∆U 4-5V). 110 126 and calculations based on restricted primitive model 127 showed that when the interactions between electrode-electrolyte were treated as polarizable 126 , a strong peak in DC is generated at lower voltages. Another possible mechanism that has been suggested to explain the sharp peaks in DC near PZC is related to a strong ion pairing that dissociates upon a small increase in the electrode potential.…”
mentioning
confidence: 99%